Cover Image. (10th March 2022) - Fan, Yuzhen; Scafaro, Andrew P.; Asao, Shinichi; Furbank, Robert T.; Agostino, Antony; Day, David A.; von Caemmerer, Susanne; Danila, Florence R.; Rug, Melanie; Webb, Daryl; Lee, Jiwon; Atkin, Owen K.
Abstract : The cover image is based on the Original Article Dark respiration rates are not determined by differences in mitochondrial capacity, abundance and ultrastructure in C4 leaves by Yuzhen Fan et al., https://doi.org/10.1111/pce.14267 .